THE EPIPHYTIC BRYOPHYTE FLORA OF THE COLOMBIAN AMAZON - LAURA V. CAMPOS; HANS TER STEEGE; JAIME URIBE (Caldasia)
An inventory of 384 plots on 64 trees, in four localities across the Colombian Amazon region (Amazonas, Caquetá, Putumayo, Vaupés), yielded 160 species of epiphytic bryophytes (116 of liverworts, 44 of mosses), in 64 genera and 26 families. Sampling was carried out in four non-seasonally flooded forests (Terra Firme), where bryophytes where collected from the base to the outer canopy, of 16 trees per locality. The flora is characterized by dominance of liverworts, especially Lejeuneaceae. The families with the highest number of records were Lejeuneaceae (55%), Calymperaceae (10%), Lepidoziaceae (8%), Octoblepharaceae (6%) and Sematophyllaceae (5%). The most common genera in number of records were Cheilolejeunea (11%), Pycnolejeunea (8%), Archilejeunea (8%) Ceratolejeunea (8%) and Syrrhopodon (7%).Syrropodon and Lejeunea were the most species-rich genera, followed by Ceratolejeunea and Cheilolejeunea. In average, the localities had 102 species in sixteen phorophytes. In terms of species richness and composition there were no significant differences between the four localities.